The Indirect Effect of Posttraumatic Stress Disorder Symptoms on Current Alcohol Use Through Negative Cognitions in Sexual Minority Men. Issue 4 (20th July 2018) - Banerjee, Nikhil; Ironson, Gail; Fitch, Calvin; Boroughs, Michael S.; Safren, Steven A.; Powell, Alexis; O'Cleirigh, Conall
Abstract: Self‐medication theory posits that some trauma survivors use alcohol to cope with posttraumatic stress disorder (PTSD) symptoms, but the role of negative posttraumatic cognitions in this relationship is not well defined. We examined associations among PTSD symptoms, posttraumatic cognitions, and alcohol intoxication frequency in 290 men who have sex with men (MSM), who reported a history of childhood sexual abuse (CSA). Using a bootstrap approach, we examined the indirect effects of PTSD symptoms on alcohol intoxication frequency through posttraumatic cognitions regarding the self, world, and self‐blame. In separate regression models, higher levels of PTSD symptoms and posttraumatic cognitions were each associated with more frequent intoxication, accounting for 2.6% and 5.2% of the variance above demographics, respectively. When examined simultaneously, posttraumatic cognitions remained significantly correlated with intoxication frequency whereas PTSD symptoms did not. Men reporting elevated posttraumatic cognitions faced increased odds for current alcohol dependence, odds ratio ( OR ) = 2.19, 95% CI [1.13, 4.22], compared with men reporting low posttraumatic cognitions, independent of current PTSD diagnosis. A higher level of PTSD symptom severity was indirectly associated with more frequent alcohol intoxication through cognitions about the self and world; the indirect to total effect ratios were 0.74 and 0.35, respectively. Negative posttraumatic cognitions pertaining to individuals' self‐perceptions and appraisals of the world as dangerous may play a role in self‐medication with alcohol among MSM with a history of CSA. Interventions targeting these cognitions may offer potential for reducing alcohol misuse in this population, with possible broader implications for HIV‐infection risk.